Fostering, Child Welfare, and Ethnic Cultural Values - Eliane El Badaoui; Lucia Mangiavacchi (Institute of Labor Economics (IZA), 2018)
This article examines the effects of fostering on children's labour supply and schooling in host families in Niger. The focus is on the causal role of ethnic inherited cultural values and behaviours in perpetuating fostering. In particular, at the ethnic group level, we rely on the inherited level of community integration, the situation of frequent interethnic violence, and an indicator of great importance attributed to foster parents. We specify a simultaneous equations model with three outcomes for children (school attendance, hours of market work and hours of domestic work) and a treatment variable (fostering). The results show that foster children are more likely to attend school and to have longer hours of domestic work than biological children. Importantly, we find evidence of a schooling fostering for boys and a domestic fostering for girls. We provide heterogeneous effects for different samples and test the robustness of the results to different empirical specifications. All in all, ethnic inherited values and behaviours are found to have an important causal effect on children's welfare.
Keywords: J13; J22; O12; C34; 330; child fostering; culture; child labour; domestic work; schooling; Niger